(untitled) (Al-Mansour Journal, 2023)
The paper discusses the development of depository law and A authorship law and the endeavors of (WIPO) organization in protecting the intellectual property right in Iraq It also discusses the significance of watermarking and how can be implemented in highly valued multimedia. It is found that both laws deal with conventional media. Nowadays we have to think of using and producing multimedia data so, the paper suggests that we have to a mend both laws, in addition to initiate a law for digital copyright to protect digital watermarking in case there have been a highly valued digital intellectual works and production.